2014
DOI: 10.1002/jbmr.2378
|View full text |Cite
|
Sign up to set email alerts
|

A Single Nucleotide Polymorphism in Osteonectin 3′ Untranslated Region Regulates Bone Volume and Is Targeted by miR-433

Abstract: Osteonectin/SPARC is one of the most abundant non-collagenous extracellular matrix proteins in bone, regulating collagen fiber assembly and promoting osteoblast differentiation. Osteonectin-null and –haploinsufficient mice have low turnover osteopenia, indicating that osteonectin contributes to normal bone formation. In male idiopathic osteoporosis patients, osteonectin 3’ UTR single nucleotide polymorphism (SNP) haplotypes that differed only at SNP1599 (rs1054204) were previously associated with bone mass. Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 46 publications
(107 reference statements)
0
49
0
Order By: Relevance
“…ON is synthesized by preosteoblasts and has less affinity to collagen. The ON transcript is quite stable, with a half-life of > 24 h under conditions of transcription arrest [Dole et al, 2015], and it can thus be concluded that the earlier synthesized ON, via the H. perforatum L.-treated DP-MSCs and BM-MSCs, accelerated osteogenic differentiation. The preosteoblasts matured on approximately day 14, and OCN was synthesized by these mature osteoblasts and marked the late phase of osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…ON is synthesized by preosteoblasts and has less affinity to collagen. The ON transcript is quite stable, with a half-life of > 24 h under conditions of transcription arrest [Dole et al, 2015], and it can thus be concluded that the earlier synthesized ON, via the H. perforatum L.-treated DP-MSCs and BM-MSCs, accelerated osteogenic differentiation. The preosteoblasts matured on approximately day 14, and OCN was synthesized by these mature osteoblasts and marked the late phase of osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…Hypericum perforatum L., also known as St. John's wort [Oztürk et al, 2007], is known to have remarkable wound-healing and anti-inflammatory properties [Knüp-pel and Linde, 2004;Dole et al, 2015]. It is used to treat anxiety, depression, lacerations, burns, cancer, and bacterial and viral diseases, and is an antioxidant, analgesic, and neuroprotective agent [Rota et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…ON is an early marker of osteogenesis that is synthesized by preosteoblasts and has less affinity to collagen. The ON transcript is quite stable, with a half-life of >24 hours under conditions of transcription arrest [23]. So we suggested that O. basilicum may accelarate the ostegenic differentiation in both DP-and BM-MSCs since the ON level was reduced signed to loose the stability being secreted early.…”
Section: Differentiation Assays Of Mscsmentioning
confidence: 87%
“…ON is an early marker of osteogenesis that is synthesized by preosteoblasts and has less affinity to collagen. The ON transcript is quite stable, with a half-life of >24 hours under conditions of transcription arrest 16 . The T. spicata var.…”
Section: Discussionmentioning
confidence: 99%